Methodology of maintenance of arrival flow integrity based on the characteristics of the permanent reduction mode - V. B. Malygin (Научный вестник МГТУ ГА)
The article deals with the technique of constructing standard arrival routes using the CDO profile in the airspace of the "approach" zone with increased air traffic intensity. The methodology for calculating the effective values of airspace structure elements is based on the probabilistic characteristics of the arrival flow, on the basis of which the required working areas of the «trombone» and «point merge» are determined in an iterative way in order to maintain the CDO regime. As a result of the application of this technique, an exemplary structure is presented from three standard arrival routes for Sheremetyevo Airport, in which trombones are used on the final sections of the arrival route. The calculation of the probabilistic characteristics of the unimportant functioning of a «trombone» («point merge») is made proceeding from the Poisson law of the arrival flow of the aircraft for each route and the uniform distribution of the random value of the aircraft entry of all routes to an elementary common segment (l). A comparative evaluation of the efficiency of the “trombone” and “point merge” circuits on the working area is made on the basis of the characteristics of the aircraft traffic flow. An important result is obtained, mainly on the “trombone” type, not only on the efficiency of airspace use, but also on the integrity characteristics of the aircraft arrival required for CDO. The obtained results are confirmed by the simulation carried out under the conditions of the problem. In conclusion, the conditions for the practical provision of a constant reduction regime at CDO sections of the standard arrival routes are presented, which includes the exceedance of the calculated ATM, and measures are proposed to minimize the negative consequences from such disturbances of the incoming flow.